2011
DOI: 10.1118/1.3658728
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical comparison of x-ray angiographic image quality using energy-dependent and conventional subtraction methods

Abstract: While the energy-based methods are not necessarily optimized and further improvements are likely, the linearized noise-propagation analysis provides the theoretical framework of a level playing field for optimization studies and comparison with conventional DSA. It is concluded that both dual-energy and photon-counting approaches have the potential to provide similar angiographic image quality to DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

9
0

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 63 publications
2
45
1
Order By: Relevance
“…Spectroscopic x‐ray imaging detectors are under development in academic and industry laboratories. Advantages of spectroscopic detectors over energy‐integrating detectors include improved dose efficiency and the potential for single‐exposure, material‐specific imaging …”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic x‐ray imaging detectors are under development in academic and industry laboratories. Advantages of spectroscopic detectors over energy‐integrating detectors include improved dose efficiency and the potential for single‐exposure, material‐specific imaging …”
Section: Introductionmentioning
confidence: 99%
“…There is reason to believe that dual-energy methods, called energy-subtraction angiography (ESA) in this paper, can compete directly with DSA to produce high-quality angiographic images for the same patient exposure. For example, Tanguay 34 compared image quality using DSA, ESA, and photon-counting-based energy-resolving angiography (ERA) with a theoretical model that was validated using a Monte-Carlo simulation. They concluded that ESA and ERA could, in principle, produce comparable image quality in terms of iodine SNR relative to DSA at low iodine concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 This spectral separation is typically achieved by kVp switching, 14 where a first image is taken using a low x-ray tube voltage (kVp) and, immediately after, a second image is obtained with a high kVp. While this minimizes the overlap in the images’ spectra, the temporal separation between the two images makes this technique very sensitive to motion artifacts, an issue of particular importance when dealing with both cardiac 15 and pulmonary imaging.…”
Section: Introductionmentioning
confidence: 99%